Specific Properties of Woven Multiaxial Structures - Czekalski, Bartłomiej; Snycerski, Marek (Instytut Biopolimerów i Włókien Chemicznych (IBWCh) , Łódź, Polska, 2014)
The development of the construction and technology of multiaxial fabrics should be accompanied by exploring their specific properties. On the one hand, there is a need to assess the behaviour of such woven structures under complex loading, while on the other there are no appropriate tools to conduct such research. This paper presents a prototype of a bi-directional load testing machine which was used to generate complex stress in tri- and foura-xial fabrics. Fabrics used for the tests were made of woven polyester tapes subjected to the thermal stabilisation process in order to unify their properties. As was expected, the results confirmed that increasing the number of axes in the fabric results in improved directional properties and increases the transfer of oblique loads in relation to the main axis. In the case of multiaxial fabrics, longitudinal rigidity in both directions can be increased by either increasing the number of axes or reducing working-in of threads (tapes) in the fabric. A multiaxial fabric may replace a package composed of many orthogonal fabrics when reinforcement of a composite exposed to complex multidirectional loading is required.
Keywords: multiaxial woven structure; fabric mechanical properties; testing machine